2010
DOI: 10.1111/j.1532-950x.2010.00659.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Attachment Sites and Joint Angle at the Time of Lateral Suture Fixation on Tension in the Suture for Stabilization of the Cranial Cruciate Ligament Deficient Stifle in Dogs

Abstract: LSS as commonly performed is associated with a significant increase in suture tension on flexion of the stifle, potentially over-constraining the joint. Tightening should be performed with the stifle in slight extension rather than in flexion.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
76
1
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 46 publications
(85 citation statements)
references
References 18 publications
3
76
1
5
Order By: Relevance
“…An ex vivo study showed that double holes at the tibial crest had the least change in suture tension across the range of motion in canine stifle joint, compared to other lateral suture attachments points (e.g., Flo method and so on). 9 However, there was no report about the efficacy of this method in clinical cases. Our study showed that this method might be excellent among LFS methods.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…An ex vivo study showed that double holes at the tibial crest had the least change in suture tension across the range of motion in canine stifle joint, compared to other lateral suture attachments points (e.g., Flo method and so on). 9 However, there was no report about the efficacy of this method in clinical cases. Our study showed that this method might be excellent among LFS methods.…”
Section: Discussionmentioning
confidence: 99%
“…Tightening should be performed with the stifle in slight extension rather than in flexion. 9 However, there has been no report about the surgical results of two-hole LFS techniques for canine CRCL rupture. Further, in general, risk factors for CRCL rupture include large, active dogs, obesity, and animals that participate in the weekend warrior syndrome (intermittent excessive activity by inactive dogs and their owners).…”
Section: Introductionmentioning
confidence: 99%
“…Porém, independentemente do ponto exato de fixação da sutura lateral, mudanças consideráveis na tensão desta podem ocorrer durante o movimento da articulação. Essa mudança na tensão aumenta significativamente com a flexão da articulação, podendo neste momento exercer excessiva pressão sobre o compartimento lateral do joelho, causando possível desequilíbrio na distribuição de carga das superfícies articulares e dos meniscos (Fischer, et al, 2010;Tonks et al, 2010).…”
Section: Introductionunclassified
“…Contudo, independentemente do ponto exato de fixação da sutura lateral, mudanças substanciais na tensão desta podem ocorrer durante o movimento da articulação. Essa mudança na tensão aumenta significativamente com a flexão da articulação (FISCHER, et al, 2010;TONKS et al, 2010).…”
Section: Introductionunclassified